Improving the Effectiveness of Green Local Development The Role and Impact of Public Sector-Led Initiatives in Renewable Energy - Martinez-Fernandez, Cristina (OECD Green Growth Papers, 2013)
This report presents a snapshot of the global renewable energy industry and investigates what this global industry can mean for local development. This industry is rapidly growing in response to countries' activities to reduce their carbon emissions. The deployment of renewable energy is seen as a key development opportunity for rural regions and a way for governments to give substance to "green growth" claims. The paper suggests that local governments and other institutions will be central agents in the success of the transition of regional areas to low-carbon economies